2019
DOI: 10.1039/c9ob00797k
|View full text |Cite
|
Sign up to set email alerts
|

A straightforward TBHP-mediated synthesis of 2-amidobenzoic acids from 2-arylindoles and their antimicrobial activity

Abstract: Synthesis of 2-amidobenzoic acids has been achieved through TBHP-mediated oxidative ring opening of 2-arylindoles. The synthesized compounds have been evaluated for their antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Based on the above results and literature reports, , a plausible mechanistic pathway is illustrated in Scheme . First, tert -butoxyl and tert -butylperoxy radicals are easily formed by the exposure of TBHP to n -Bu 4 NI, , which initiates hydrogen abstraction of 1 to afford indolyl radical A and its resonance species B .…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Based on the above results and literature reports, , a plausible mechanistic pathway is illustrated in Scheme . First, tert -butoxyl and tert -butylperoxy radicals are easily formed by the exposure of TBHP to n -Bu 4 NI, , which initiates hydrogen abstraction of 1 to afford indolyl radical A and its resonance species B .…”
mentioning
confidence: 66%
“…These results suggested that a free radical process was involved in the reaction. It was initiated by hydrogen abstraction of N–H bonds of indoles with tert -butoxyl or tert -butylperoxy radicals (vide infra) . The addition of 15 equiv of H 2 18 O to the reaction produced 3a in 68% yield without observation of 18 O-labeled product (Scheme , eq 2), which suggested that the carbonyl oxygen atom of the product came from TBHP .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TBHP-catalysed synthesis of 2-amidobenzoic acids was reported by Patel and co-workers in 2019. [28] The oxidative ring opening reaction condition was adjusted by employing 2phenylindole (71) as model substrate. The model reaction attempted in presence of TBHP (3 equiv.)…”
Section: Cà O Bond Formation Via Radical Pathwaymentioning
confidence: 99%
“…2-Arylindoles are central structural motifs in many pharmaceutically active compounds . Due to the inherent electron-richness of 2-arylindoles, oxidative-dearomative ring-opening transformations with different nucleophiles have recently been studied to access several heteroaromatic compounds. Yan et al recently developed an interesting approach for synthesizing 2,3-diarylquinoxalines through NIS-mediated ring opening of 2-arylindoles with 1,2-diamino benzenes (Scheme b) . Besides, electrochemical organic transformations that use electrons as reagents for oxidative/reductive conversion and an excellent functional group tolerance under benign conditions have recently been influential in expanding modern organic synthesis. Developing an environmentally benign organic-electrosynthesis approach for constructing privileged heterocycles has become a fascinating goal for synthetic chemists.…”
Section: Introductionmentioning
confidence: 99%